2013
DOI: 10.1140/epjb/e2013-31025-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic centrality — is there an underestimated epidemic impact of network peripheral nodes?

Abstract: In the study of disease spreading on empirical complex networks in SIR model, initially infected nodes can be ranked according to some measure of their epidemic impact. The highest ranked nodes, also referred to as "superspreaders", are associated to dominant epidemic risks and therefore deserve special attention. In simulations on studied empirical complex networks, it is shown that the ranking depends on the dynamical regime of the disease spreading. A possible mechanism leading to this dependence is illustr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…In addition, they showed that for small t, degree centrality is better than eigenvector centrality while for very large t, eigenvector centrality is much better. Note that, the Ghanbarnejad-Klemm method [174] is not a really time-aware method since the eigenvector of M contains no temporal information, however, their simulation results have clearly demonstrated the significance of temporal factor, similar to the contribution byŠikić et al [157], who have showed the relevance of dynamical parameters. Liu et al [51] proposed a so-called dynamics-sensitive (DS) centrality to predict the outbreak size at a given time step t, which can be directly applied in quantifying the spreading influences of nodes.…”
Section: Time-aware Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, they showed that for small t, degree centrality is better than eigenvector centrality while for very large t, eigenvector centrality is much better. Note that, the Ghanbarnejad-Klemm method [174] is not a really time-aware method since the eigenvector of M contains no temporal information, however, their simulation results have clearly demonstrated the significance of temporal factor, similar to the contribution byŠikić et al [157], who have showed the relevance of dynamical parameters. Liu et al [51] proposed a so-called dynamics-sensitive (DS) centrality to predict the outbreak size at a given time step t, which can be directly applied in quantifying the spreading influences of nodes.…”
Section: Time-aware Methodsmentioning
confidence: 83%
“…Sikić et al [157] raised a very important issue, but their solution is not a real solution since if we can accurately calculate the epidemic centrality, we should know every details of this dynamics and we must have done all possible simulations, so that we do not need to know epidemic centrality again because given any parameter pair (β, δ), we already have the corresponding ranking of nodes' influences. Evolutionary games have long been exemplary models for the emergence of cooperation in socioeconomic and biological systems [175,176].…”
Section: Othersmentioning
confidence: 99%
“…However, the tables give little insight as to why effective resistance outperforms the other quantities. To gain intuition, we look at the heatmaps of the Lesmis network [23] in Figure 4 representing the importance of each node according to the respective graph quantity. We see that effective resistance and the epidemic hitting time are the only two graph quantities that assign relative importance to peripheral nodes of the network.…”
Section: B Centralitiesmentioning
confidence: 99%
“…Van Mieghem et al [12] propose that the best conduction node in a resistor network is the minimizer of the diagonal elements of the pseudoinverse matrix Q † of the weighted Laplacian matrix of the graph. In the Susceptible-Infected-Removed (SIR) model [13], Sikić et al [14] show that the ranking of nodal influences is sensitive to the spreading dynamics, which depends on the a e-mail: Z.He@tudelft.nl infection rate and the curing rate. Measured by the cumulative infection probabilities of nodes, the degree centrality can better identify influential spreaders when the spreading rate is very small.…”
Section: Introductionmentioning
confidence: 99%